Thromboinflammation vs. immunothrombosis: strategies for overcoming anticoagulant resistance in COVID-19 and other hyperinflammatory diseases. Is ROTEM helpful or not? - Almskog, Lou M.; Ågren, Anna (Frontiers in Immunology, 2025)
Thrombosis and inflammation are closely interconnected. Systemic inflammation activates the coagulation system, while components of the coagulation system can, in turn, significantly influence the inflammatory response. This process, where the immune system contributes to thrombus formation, is known as immunothrombosis. Conversely, thromboinflammation describes the effect of thrombus formation on the immune system. Various immune cells, including neutrophils and monocytes, play key roles in these processes, as well as endothelial cells, strategically positioned to rapidly detect and respond to invading pathogens. Platelets are also actively recruited, promoting coagulation and releasing procoagulant factors. When the endothelium becomes dysfunctional and acquires proinflammatory and procoagulant properties, it fosters the formation of microvascular thrombosis. The excessive release of proinflammatory cytokines and chemokines further intensifies this cycle, contributing to cytokine storms, as observed in severe COVID-19 cases. This phenomenon exemplifies immunothrombosis and thromboinflammation. Anticoagulant therapy is standard care for venous thromboembolism prevention in Intensive Care Unit patients, with critically ill COVID-19 patients often receiving higher doses. However, variations in individual responses to heparin were observed in COVID-19 patients, suggesting a degree of resistance to anticoagulant therapy. This resistance may be linked to thromboinflammation, where the intense inflammatory response diminishes the effectiveness of anticoagulation. In this context, combining anticoagulants with immunomodulatory drugs has shown promising potential. This review aims to delve into the concepts of immunothrombosis and thromboinflammation, with a particular focus on the complex interplay between the coagulation and inflammation systems and their mutual reinforcement in the context of COVID-19. We examine why standard anticoagulant therapies often proved insufficient in managing hyperinflammatory diseases and discuss potential alternative treatment strategies. Furthermore, we evaluate the potential role of rotational thrombelastometry (ROTEM) in managing immunothrombotic states.